2011
DOI: 10.5047/eps.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Statistic analysis of swarm activities around the Boso Peninsula, Japan: Slow slip events beneath Tokyo Bay?

Abstract: Seismicity re ects underground stress states, satisfying scaling laws such as Gutenberg-Richter law and OmoriUtsu law. Standard seismicity models based on these scaling laws, such as the Epidemic Type Aftershock Sequence (ETAS) model, are useful to identify swarm anomalies in seismicity catalogs. Llenos et al. (2009) applied the ETAS model to swarms triggered by slow slip events (SSEs) and found that stressing rate controls the background seismicity μ suggesting that swarms can be utilized to monitor stress ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
2
29
1
Order By: Relevance
“…A majority of seismicity accompanying SSEs is observed to have swarm-type behaviour (e.g. Llenos et al 2009;Okutani & Ide 2011;Vallee et al 2013). There is no unique declustered catalogue, because we do not know which events are truly independent.…”
Section: Method: Declustering and Calculations Of Probabilitiesmentioning
confidence: 96%
“…A majority of seismicity accompanying SSEs is observed to have swarm-type behaviour (e.g. Llenos et al 2009;Okutani & Ide 2011;Vallee et al 2013). There is no unique declustered catalogue, because we do not know which events are truly independent.…”
Section: Method: Declustering and Calculations Of Probabilitiesmentioning
confidence: 96%
“…For example, the window from 1 January 1992 to 31 December 2001 includes seismicity from 1 January 1990 to 31 December 1991. For events in a given region and time window, five ETAS parameters were determined (µ,α,c,K and p) using a nonlinear inversion code 9,19 . As the result of nonlinear inversion generally depends on the set of initial values, the initial values were changed at least 100 times to obtain the maximum likelihood solution.…”
Section: Methodsmentioning
confidence: 99%
“…As the result of nonlinear inversion generally depends on the set of initial values, the initial values were changed at least 100 times to obtain the maximum likelihood solution. The error bound for each ETAS parameter was estimated with the two-sigma rule using a Hessian matrix 19 . Although all five parameters were determined, here I focus on µ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such events occurred in October 2002, August 2007, and October 2011 [e.g., Ozawa et al ., ]. Earlier studies showed that during the swarm periods of 2002 and 2007, the background seismicity rates were elevated by approximately 1 or 2 orders of magnitude [ Llenos et al ., ; Okutani and Ide , ].…”
Section: Applications To Induced Inland Seismicitymentioning
confidence: 99%